Qualitative data analysis an introduction - Grbich, Carol (London SAGE Publications Ltd., 2013)
This fully updated and expanded second edition provides a guide through current issues in the analysis of qualitative data. Packed with detailed examples, a glossary, further reading lists and a section on writing up, this book is exactly what you need to get you started in qualitative research. The new edition covers analytical approaches including: - grounded theory - classical, existential and hermeneutic phenomenology - feminist research including memory work - classical, auto- and cyberethnography as well as ethnodrama - content, narrative, conversation and discourse analysis - visual interpretation - semiotic, structural and poststructural analyses A one-stop-shop for students new to qualitative data analysis!
Keywords: Qualitative research; Social sciences -- Research